2015
DOI: 10.1111/nph.13470
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting SNPs for biallelic CRISPR mutations in the outcrossing woody perennial Populus reveals 4‐coumarate:CoA ligase specificity and redundancy

Abstract: CRISPR (clustered regularly interspaced short palindromic repeats), first discovered as an immune system of prokaryotes, has become a powerful tool for genome editing in eukaryotes (Gaj et al., 2013). Co-expression of the CRISPR-associated endonuclease (Cas9) with a chimeric guide-RNA (gRNA) targeting a GN 19 NGG motif results in a double-strand DNA break near NGG, the protospacer adjacent motif (PAM) (Jinek et al., 2012). Processing by the endogenous DNA repair machinery generates small indels that, when loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
218
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(230 citation statements)
references
References 19 publications
5
218
0
2
Order By: Relevance
“…A "substituted genome sequence of P. tremula x alba INRA 717-1B4" (sPta717) was created "by introducing genomic variants of INRA 717-1B4 into the P. trichocarpa reference genome" using 20x resequencing NGS (next generation sequencing) data (v1.1 of sPta717 at http://aspendb.uga.edu/index.php/ databases/spta-717-genome; Zhou et al, 2015). This resource has been applied for screening of 717 gRNAs for sequence variants to optimize gRNA design in CRISPR/Cas genome editing experiments (Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A "substituted genome sequence of P. tremula x alba INRA 717-1B4" (sPta717) was created "by introducing genomic variants of INRA 717-1B4 into the P. trichocarpa reference genome" using 20x resequencing NGS (next generation sequencing) data (v1.1 of sPta717 at http://aspendb.uga.edu/index.php/ databases/spta-717-genome; Zhou et al, 2015). This resource has been applied for screening of 717 gRNAs for sequence variants to optimize gRNA design in CRISPR/Cas genome editing experiments (Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that C. cellulolyticum might have less active NHEJ-based repair pathways. On the other hand, ''nickase type'' Cas9n had been shown to induce highly efficient ([95 %) HR-based gene targeting at the targeted locus [74]. This high gene targeting efficiency will open the door to high-throughput molecular genetics in wood decay bacteria.…”
Section: Challenges For Genome Engineering Of Woody Plants and Wood Dmentioning
confidence: 99%
“…Most recently, Zhou et al [74] demonstrated the successful gene knockout of 4-coumarate:CoA ligase, the 4CL1 gene in Populus tremula 9 alba clone 717-1B4. The 4CL1 gene is a key gene in lignin biosynthesis [17,75].…”
Section: Challenges For Genome Engineering Of Woody Plants and Wood Dmentioning
confidence: 99%
“…최근 들 어 세균 획득 면역반응 system (CRISPR/Cas9(clustered Regularly Interspaced Short Palindromic Repeats/ CRISPR-associated protein 9)은 염기서열 특이적 핵산분해효소로서 작용할 수 있는 일 종의 맞춤형 유전자가위이다. CRISPR/Cas9 활용을 통해 특 정염기서열을 인지하고 그 부위의 이중나선을 절단함으로 써 유전체상 위치 특이적 돌연변이 유도, 유전자삽입, 대체 등을 포함한 다양한 염기서열 특이적 유전체 편집이 가능 하다 (Endo et al 2016;Wang et al 2016;Zhou et al 2015;Jiang et al 2013). 지금까지 많은 생물에서 CRISPR/Cas9를 이용하여 유전자 편집에 대한 보고는 되었으나 일반적인 연구실에서 적용 및 응용하기가 아직 부족한 실정이다.…”
unclassified